AMLO contre le cannabis : le tout-puissant veto présidentiel à la trajectoire de légalisation du cannabis au Mexique - Luis Rivera-Vélez (Cahiers des Amériques Latines)
The failure of the cannabis legalization process in Mexico illustrates how President AMLO becomes an almighty veto player compared to his predecessors. Using the veto player framework and based on a qualitative survey to trace the details of the decision-making process, the paper shows that the president acquires exceptional blocking powers through two main techniques. First, AMLO comes to power with absolute parliamentary majorities, which allows him to absorb the veto capacities of parliamentary institutions. Secondly, AMLO gradually neutralizes the powers of by-passing institutions, promising to put the decision to a referendum, contesting the Supreme Court’s decisions, or establishing a pro-cannabis bureaucracy completely dependent of the presidency. Since AMLO’s rise to power, any hope of cannabis legalization evaporated in Mexico, despite an alignment of political forces in favor at the national level and a regional tendency to relax cannabis prohibition.